City of Poets Dreaming: Cross-cultural Poetics in the Case of Macao - Kelen, University of Macau, Christopher (Asiatic: IIUM Journal of English Language and Literature, 2012)
Poetry of a place is important for making us look again and not merely take for granted the objects and the activities going on around us. The criterion is definitive in the sense that the poem which does not make us look again is not really worth attending to. Thereâ€™s reflexive potential in that process of â€œre-visioningâ€ because it maximises the chances of our seeing ourselves in the mirror which the poem-of-place naturally is. Â Â Â  Contemporary Macao poetry â€“ written in Chinese, in Portuguese and in English â€“ should by no means be seen as the beginning of an East/West conversation; we can take it for granted that Macao poets today are the inheritors of varied traditions. Indeed, one might wish to claim that it is the mix of influences which gives contemporary Macao poetry its life. But Macao poetry is not merely the result of a hybrid position between traditions; it is a poetry deeply concerned with place and identity. The present paper is interested in how this particular artefact of culture (a poetry) represents place through an encounter between cultures. Such an interest conveniently situates the idea of poetry as practice of â€œplace-based aesthetics,â€ along the lines suggested by Raymond Williamsâ€™ â€œradical particularity.â€ Â Â Â  Dreams are a major preoccupation in Macao poetry today and this paper works to connect various oneiric encounters offered in the poetry with both the symbolic potential of Macao and with its reality as witnessed, historically and today.